Analysis of Reward and Punishment at Bank BTPN KCP Sumedang - Sumiati, Ai; Septian, Tedy (SINTESA, 2024)
Reward and Punishment are two words that are contradictory to each other, however, these two things are interrelated, both of which spur employees to improve the quality of work. Reward and Punishment are closely related to motivating employees, including employees working in banking and non-banking institutions. Based on this, this study aims to find out the implementation of reward and punishment at Bank BTPN KCP Sumedang. The results of this study show that Bank BTPN KCP Sumedang has implemented rewards and punishments for employees. Implementation of rewards at Bank BTPN KCP Sumedang in the form of extrinsic rewards such as salaries, benefits, bonuses, training, promotions and growing intrinsic rewards for employees such as a sense of pride in completing work and achieving targets. Meanwhile, the punishment applied to Bank BTPN KCP Sumedang is in the form of verbal warning, written warning and the provision of SP1 SP2 SP3 and severe punishment will not extend the contract and layoffs (termination of employment). With the application of reward and punishment can improve employee performance. It is hoped that Bank BTPN KCP Sumedang will be able to further increase rewards so that employee work productivity increases. Because reward and punishment have a positive influence, can improve employee performance and as a form of mutual prosperity between employees